1970
DOI: 10.1128/aem.20.2.263-270.1970
|View full text |Cite
|
Sign up to set email alerts
|

Production of Nucleic Acid-Related Substances by Fermentation Processes

Abstract: Inosine-producing cultures were found among mutants resistant to 6-mercaptoguanine (6MG) derived from a 5'-inosinic acid (IMP)-producing strain, KY 13102, of Brevibacteriwn ammoniagenes. Inosine-producing ability was very frequent among the mutants resistant to a low concentration (10 to 50 tzg/ml) of 6MG. The accumu

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1975
1975
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Meanwhile, it was reported that inosine (IR) was accumulated in place of 5'inosinic acid (5'IMP) by mutants which are devoid of nucleoside degrading activity and induced from 5'IMP accumulating strain of B. ammoniagenes. 7,8) In this report, efficient conversion of 6AU to 6AUR was aimed and a suitable strain was selected from IR produc ing mutants of B. ammoniagenes. Further more, conditions for the conversion and genetical improvement of the strains was carried out, resulting in accumulation of more than 12mg of 6AUR per ml.…”
mentioning
confidence: 99%
“…Meanwhile, it was reported that inosine (IR) was accumulated in place of 5'inosinic acid (5'IMP) by mutants which are devoid of nucleoside degrading activity and induced from 5'IMP accumulating strain of B. ammoniagenes. 7,8) In this report, efficient conversion of 6AU to 6AUR was aimed and a suitable strain was selected from IR produc ing mutants of B. ammoniagenes. Further more, conditions for the conversion and genetical improvement of the strains was carried out, resulting in accumulation of more than 12mg of 6AUR per ml.…”
mentioning
confidence: 99%